The communication of innovation: an empirical analysis of the advancement of innovation - Malte Ackermann (Philipps-University Marburg, Department of Technology and Innovation Management, 2013)
The notion that the word Innovation has been excessively used in various contexts has been stated numerous times, still there is no study which empirically examines this issue. This paper addresses this research gap by utilizing a quantitative content analysis on almost 4 billion documents in the News segment of the Database LexisNexis. The sample period ranges from 1980 to 2010 and allover encompasses 2,013,143 documents containing the word Innovation. The Augmented Dickey-Fuller test indicates that the time-series data is non-stationary and has to be integrated in order-one. The results of the regression analysis illustrate that the documents containing Innovation of the preceding year significantly predict the next year, indicating past dependencies. The quantitative content analysis showed that the relevance of the word Innovation has progressed by 132.62% from the beginning of the sample period (1980) to the end of the sample period (2010). From 1980 to 1994 the indications of Innovation remained relatively constant around 0.003% of the documents. In 1995 the importance of Innovation apparently begins to rise to the year 2000 when it reaches its peak. In 2001 the indication of Innovation begins to decline slightly again, but advances towards the end of the sample period again. In general, these findings indicate that the word Innovation has been used quite more often within the last decades, reaching its peak of usage around the turn of the millennium.
Keywords: 650; Innovation; Communication; Quantitative Content Analysis